Preparation of a novel chitosan derivative and use in water treatment - Min Zhang; ChengYu Tan; Liang Kong; LuChen Jin (2011 International Conference on Multimedia Technology, 2011)
Chitosan-betaine derivative was prepared by chitosan and betaine hydrochloride through dry process in the presence of dicyandiamide. The product exhibited solubility, practical flocculating property and antibacterial efficacy.